EL ROL DEL CAPITAL INTELECTUAL EN LA INNOVACIÓN DE LAS EMPRESAS (ARTÍCULO DE REVISIÓN) - María del Carmen Cano Alvarado; Guillermo César Sánchez Martínez; Manuel González Pérez; Juan Carlos Pérez García (European Scientific Journal, ESJ, 2014)
The purpose of this article is to show the relationship of the intellectual capital of companies and innovativeness of the products and services they placed on the market. Intellectual capital (IC) is the sum of human, structural and relational resources that exist in the company, as well as the interplay between them established it. Innovation is the transforming power of the company. If a company does not invest intellectual capital to promote the development of innovation capabilities, this competitive advantage will be diminished. This article is a review of the literature published in various sources. It includes the Academy of Management Journal, Academy of Management Journal, Journal of knowledge management, Journal of Human Resource Costing & Accounting and the Journal of Intellectual Capital. The results of the literature review reveal that IC management influences innovation capabilities of companies, whether radical or incremental.